Living in space - Bowman, Lucy Author; Wheatley, Abigail Author; Mayani, Rafael (London Scholastic, 2021)
Where do people live in space? How do they get there? What's it like to work, eat and sleep in space? Beginner readers can discover the answers to these questions and lots of other fascinating facts in this engaging information book. With simple text and stunning photographs and illustrations, plus links to websites with video clips and activities.
Grade 4
eng